Why language of instruction in moral education is an issue for socially just policies in plural societies - Abdullah, Nur Surayyah Madhubala; Yasin, Maizura; Saharuddin, Norzihani (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
The paper presents an argument that the current account of social justice in Moral Education in Malaysia is too limited. That account concerns itself only with the outcomes of moral education framed in the well-being of others. It is located in the ethical percept of utility. We argue that it should also concern itself with the outcomes for the student framed in terms in terms of their well-being as persons whereby their individual educational experiences should be given due consideration in the concept of justice adopted. We begin by elucidating moral education in Malaysia. We note that usual accounts of equity and justice in moral education are concerned with and valued for its significance to a person’s life- their flourishing as moral persons. We point out how the current account of social justice in Moral Education lacks such concern. There is little clarity about the contribution of such experiences to their well-being as persons with different ideas about morality. We offer a provisional account of the educational goods in experiences of moral education, and compare this to emerging research on language of instruction in moral development concluding that the significance of the language of instruction in the teaching and learning of Moral Education should be recognised within educational policy on Moral Education for Malaysia’s plural society.